2022
DOI: 10.4308/hjb.29.2.214-221
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity of Endophytic Bacteria Derived from Hoya multiflora Blume Plant and Their Cellular Activities on Schizosaccharomyces pombe

Abstract: Endophytic bacteria isolated from plant tissues can produce the same secondary metabolites as their host plants. One of the metabolites that the bacteria can produce is antioxidants. This research aimed to analyze and measure the antioxidant activities of two endophytic bacteria, i.e. Bacillus siamensis HMB1 and Bacillus aryabhattai HMD4 cultures, derived from Hoya multiflora Blume plant, a tropical epiphytic plant species that grows in Indonesia, and to identify their cellular effects on Schizosaccharomyces p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 42 publications
0
2
0
1
Order By: Relevance
“…Phaenibacillus and Bacillus are endophytic bacteria found in the medicinal plant Eucalyptus pellita (Susanti et al 2021). Pudjas et al (2022) reported Bacillus as endophytic bacteria derived from Hoya multiflora Blume. produced antioxidant activity.…”
Section: A B Discussionmentioning
confidence: 99%
“…Phaenibacillus and Bacillus are endophytic bacteria found in the medicinal plant Eucalyptus pellita (Susanti et al 2021). Pudjas et al (2022) reported Bacillus as endophytic bacteria derived from Hoya multiflora Blume. produced antioxidant activity.…”
Section: A B Discussionmentioning
confidence: 99%
“…Two Bacillus strains ( Bacillus siamensis , Bacillus aryabhatii ) isolated from the Hoya multiflora Blume plant showed high phenolic contents of 26.17 ± 0.48 and 16.86 ± 0.59 mg/g of gallic acid equivalents (GAE), respectively. It correlates with the high antioxidant activities of bacterial crude extract [ 70 ]. Another endophytic Bacillus sp.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of carotenoid, phenolic and flavonoid indicated these compounds might play a role as antioxidants. The correlation of phenolic and flavonoid content with the antioxidant activity of an extract already reviewed (Sariwati et al 2019;Pudjas et al 2022). Phenolic and flavonoids are known as radical scavengers, metal chelators, reducing agents, and hydrogen donors.…”
Section: Discussionmentioning
confidence: 99%
“…The total phenolic and flavonoid compounds were measured following the method described by Pudjas et al (2022). The antioxidant assay of extracts were measured through DPPH assay, which previously described by Batubara et al (2009).…”
Section: Total Phenolic Total Flavonoid and Antioxidant Activity Assaymentioning
confidence: 99%